(untitled) (Nepal Journal of Epidemiology, 2014)
Background The risk of adverse drug reaction ranges nearly from zero to high level depending upon the drug itself and the patient factor. The process of detection, assessment, monitoring and reporting of adverse drug reaction is necessary to prevent its occurrence in future. Materials and Methods Information related to suspected Adverse Drug Reactions(ADRs) were collected by pharmacists from general medical ward using ADRs reporting form from Manipal Teaching Hospital (MTH)during ward rounds. The details of suspected drug, drug reaction and all related data were documented. Naranjo Algorithm, modified Hartwig and Siegel and modified Shumock and Thornton scale were used for assessment of causality, severity and preventability respectively. All suspected ADRs were reported to National Pharmacovigilance Center and then to Uppsala Monitoring centre through the electronic online data base named Vigiflow. Results Among 1,105 patients, 51 patients experienced ADR (4.61%). Incidents of ADRs were higher with antibiotics (47.06%) and Ceftriaxone was at top of list (15.69 %). Dermatological system (25.49%) and gastrointestinal system (19.61%) were affected more. About 33.33% of suspected drugs were discontinued. About 41.18% of ADRs required medical treatment where antihistaminic (24.32%) and antipruritic (21.62%) were most commonly used to treat ADRs. To sum up, 64.71% of ADRs were probable, 62.75% were mild in nature and 60.78% were probably preventable. Conclusion Finding of the study suggests that ADRs still pose serious health threat among hospitalized patients and as a matter of fact over 60% of them are preventable. Reporting of ADR scan provide effective measures to prevent the occurrence in the future in which the role of pharmacist is vital. DOI: http://dx.doi.org/10.3126/nje.v4i1.10135 Nepal Journal of Epidemiology 2014;4 (1): 330-336